How could ICT benefit design managers for assessing sustainability of their project? - Mesut Pala; Nasreddine M. Bouchlaghem (2012)
Sustainability in the construction industry is gaining increased attention which consequently shifted the modus operandi towards improving knowledge and practice. Amongst the key stakeholders involved in the delivery of sustainable buildings are design managers, who have a vital role in terms of managing and coordinating the design process and communicating design information. During this highly complex and iterative process, design managers also undertake tasks and activities which are related to sustainability and its assessment. This study investigated the impact of sustainability assessment on the design managers’ roles and responsibilities. The research specifically focused on ICT as an ‘enabler’ within the sustainability assessment process that aids design managers in achieving a better environment while carrying out their roles and responsibilities. Without an explicit understanding about how ICT can be effectively used within the sustainability assessment process, its impact will remain limited for design managers who are one of the key players in the strive for a sustainable design process. A twofold research methodology was adopted within this project to achieve the primary and secondary research objectives, this included: an extensive literature review on the building design process, design management role and sustainability assessment; and, fieldwork, which consisted of questionnaires and series of interviews with design managers working for contractors in the industry. The research concluded that there are several barriers to the effective management of sustainability assessment by design managers caused by two major factors: the late involvement in the projects and the lack of a structured approach for the sustainability management. The study concluded that in order for ICT to become an effective ‘enabler’ in the assessment process, barriers to effective management of sustainability assessment must be removed first.